CHARACTERIZATION OF THE CHOROIDAL VASCULATURE IN MYOPIC MACULOPATHY WITH OPTICAL COHERENCE TOMOGRAPHIC ANGIOGRAPHY. Issue 9 (September 2019) - Wong, Chee Wai; Teo, Yi Chong Kelvin; Tsai, Shih Tsiang Andrew; Ting, Shu Wei Daniel; Yeo, Yew San Ian; Wong, Wen Kuan Doric; Lee, Shu Yen; Wong, Tien Yin; Cheung, Chui Ming Gemmy
Abstract : Purpose: To characterize the choriocapillaris (CC) in highly myopic eyes with myopic maculopathy, using optical coherence tomographic angiography. Methods: Prospective, clinic-based study of 42 eyes of 38 patients with high myopia (⩽−6 diopters and axial length ≥26.5 mm). Myopic maculopathy was graded from fundus photographs according to the Meta-Analysis for Pathologic Myopia classification. Macular 3 × 3 mm en face optical coherence tomographic angiographic images were obtained with swept-source optical coherence tomographic angiography and graded for CC flow impairment as follows: 1) intact CC, 2) focal (<1 mm 2 ), and 3) extensive (>1 mm 2 ). Results: Of the 42 eyes, 17 (39.5%) had tessellated fundus, 20 (46.5%) had diffuse, and 6 (14.0%) had patchy atrophy. Choriocapillaris flow impairment was observed in all eyes with diffuse and patchy atrophy. Even in eyes with tessellated fundus only, CC signal voids were seen in 3 eyes (17.6%). With increasingly severe myopic maculopathy, the pattern of CC flow impairment changed from predominantly focal to predominantly extensive. Conclusion: Choriocapillaris flow impairment was observed in many highly myopic eyes, even in those with mild fundus changes, and worsened with increasing severity of myopic maculopathy. Longitudinal studies are needed to assess whether CC flow impairment predicts the risk of myopic maculopathy progression. Abstract : Optical coherence tomographic angiography can detect choriocapillaris signal voids in highly myopic eyes without clinically apparent myopic maculopathy. The pattern of choriocapillaris signal voids changed from predominantly localized to predominantly extensive with increasing severity of myopic maculopathy.